ATIM-23. PRELIMINARY FINDINGS OF A PHASE I SAFETY AND BIOIMAGING TRIAL OF KB004 (IFABOTUZUMAB) IN PATIENTS WITH GLIOBLASTOMA. (11th November 2019) - Gan, Hui; Cher, Lawrence; Inglis, Po; Lwin, Zarnie; Lau, Eddie; Ackermann, Uwe; Coombs, Nicole; Remen, Kirsten; Guo, Nancy; Ting Lee, Sze; Gong, Sylvia; Palmer, Jodie; et al.
Abstract: Glioblastoma (GBM) is the most frequent and lethal primary brain neoplasm. EphA3 is a tumor restricted antigen expressed in 38–40% of GBM and 100% of the tumor vasculature. Ifabotuzumab is a non-fucosylated IgG1κ antibody targeting EphA3 receptor. A Phase 1 study of ifabotuzumab in haematological malignancies was well tolerated and clinically active. Here we report on a Phase I dose escalation and biodistribution study of ifabotuzumab in recurrent glioblastoma. DESIGN The primary objective is to determine the toxicity and recommended phase II dose of Ifabotuzumab in GBM patients (pts). Secondary objectives are to determine the biodistribution and pharmacokinetics (PK) of 89 Zr-Ifabotuzumab, the frequency of EphA3 positive GBM and response rates. Eligible pts received a trace (5mg) dose of zirconium-89 labelled ifabotuzumab ( 89 Zr-ifab) on day 1 followed by sequential PET imaging over 1 week to determine its biodistribution, frequency of in situ EphA3 expression and tumor uptake. Safety and PK assessments were undertaken. On Day 8, pts commenced weekly ifabotuzumab infusions until PD. Three cohorts are planned (3.5mg/kg, 5.25 mg/kg, 7.9 mg/kg). On day 36, pts received both 89 Zr-ifab and Ifabotuzumab, to assess receptor occupancy. Response rate (RANO) and survival data were collected. RESULTS: To date, 7 of 12 pts have enrolled (6 at 3.5 mg/kg, 1 at 5.25 mg/kg; Mean age: 55 years (±12.6), 4 are male). Treatment emergent AEs included infusion reactions, seizures, cerebral oedema, rash, pruritis, headaches, eye disorder. Most were considered related to study drug, seizures and infusion reactions were readily managed with increased premedications after the first occurrence. Best response in cohort 1 is SD for 23 weeks. 89 Zr-ifab PET/CT scans showed rapid, specific targeting at all known tumor sites and in all pts, but no normal tissue uptake. MRI scans showed predominant T2/FLAIR changes, occasionally marked, which were consistent with treatment effect on tumor vasculature.